Cardiac response and anxiety levels in psychopathic murderers Resposta cardíaca e nível de ansiedade em homicidas psicopatas - Antonio de Pádua Serafim; Daniel Martins de Barros; André Valim; Clarice Gorenstein (Brazilian Journal of Psychiatry, 2009)
OBJECTIVE: To compare the emotional response and level of anxiety of psychopathic murderers, non-psychopathic murderers, and nonpsychopathic non-criminals. METHOD: 110 male individuals aged over 18 years were divided into three groups: psychopathic murderers (n = 38); non-psychopathic murderers (n = 37) serving sentences for murder convictions in Maximum Security Prisons in the State of Sao Paulo; and non-criminal, non-psychopathic individuals (n = 35) according to the Psychopathy Checklist-Revised. The emotional response of subjects was assessed by heart rate variation and anxiety level (State-Trait Anxiety Inventory) after viewing standardized pictures depicting pleasant, unpleasant and neutral content from the International Affective Picture System. RESULTS: Psychopathic murderers presented lower anxiety levels and smaller heart rate variations when exposed to pleasant and unpleasant stimuli than nonpsychopathic murderers or non-psychopathic non-criminals. The results also demonstrated that the higher the score for factor 1 on the Psychopathy Checklist-Revised, the lower the heart rate variation and anxiety level. CONCLUSION: The results suggest that psychopathic murderers do not present variation in emotional response to different visual stimuli. Although the non-psychopathic murderers had committed the same type of crime as the psychopathic murderers, the former tended to respond with a higher level of anxiety and heart rate variation. OBJETIVO: Comparar a atividade cardíaca e nível de ansiedade de homicidas psicopatas e não psicopatas e não criminosos não psicopatas. MÉTODO: 110 homens com idade superior a 18 anos, divididos em três grupos: homicidas psicopatas (n = 38), homicidas não psicopatas (n = 37) cumprindo pena por homicídio em Prisões de Segurança Máxima do Estado de São Paulo e não criminosos e não psicopatas (n = 35) de acordo com a Escala de Avaliação de Psicopatia. A resposta emocional foi avaliada pela variação da freqüência cardíaca e níveis de ansiedade após a observação por seis segundos de imagens padronizadas de diferentes conteúdos emocionais (agradáveis, desagradáveis e neutras) do International Affective Picture System. RESULTADOS: Homicidas psicopatas apresentaram menores níveis de ansiedade e menor variação de frequência cardíaca quando expostos a estímulos agradáveis que os homicidas não psicopatas e o grupo de não criminosos e não psicopatas. Os resultados demonstram ainda que quanto maior o escore no fator 1 da Escala de Avaliação de Psicopatia, menor é a variação cardíaca e o nível de ansiedade. CONCLUSÃO: Os resultados sugerem que homicidas psicopatas não apresentam variação da resposta emocional frente aos diferentes estímulos visuais. Embora os homicidas não psicopatas compartilhem do mesmo tipo crime que os psicopatas, estes tendem a responder com maior nível de ansiedade e variação cardíaca.